Performance assessment of real-time precise point positioning using BDS PPP-B2b service signal. Issue 8 (15th October 2021) - Ren, Zhiling; Gong, Hang; Peng, Jing; Tang, Chengpan; Huang, Xinming; Sun, Guangfu
Abstract: China's BeiDou Navigation Satellite System (BDS) can provide real-time precise point positioning (PPP) service for users in China and surrounding areas with PPP-B2b signal. In this paper, real-time PPP is assessed and studied based on 8 days of PPP-B2b and BDS/GPS broadcast messages. Real-time precise ephemerides are compared against Multi-GNSS Experiment (MGEX) final products and the positioning performance of real-time PPP is evaluated with MGEX/iGMAS stations. Results show that the real-time orbit accuracy is about 0.0725, 0.2479 and 0.2587 m in directions of radial (R), along (A) and cross (C) for BDS-3 satellites, and 0.0729, 0.3098 and 0.2193 m for GPS satellites. The standard deviation values of the clock offset errors are about 0.05–0.18 ns for BDS-3 satellites, and 0.05–0.15 ns for GPS satellites. In addition, the differential code bias (DCB) parameters of PPP-B2b agree well with parameters of MGEX DCB and time group delay (TGD), with the differences less than 2 and 0.15 ns, respectively. Furthermore, for the positioning experiments, the average positioning accuracies of BDS and GPS integrated real-time PPP are about 1.07, 2.69 and 2.25 cm in north (N), east (E), and up (U) directions for static mode; and about 3.6, 5.9 and 9.4 cm for kinematic mode. Moreover, the convergence times for an accuracy level of 20 cm in N, E and U components are about 8–22 min, and 10–8 min, for static mode and kinematic mode, respectively.